Effects of Intermittent Hypoxia-Hyperoxia Exposure Prior to Aerobic Cycling Exercise on Physical and Cognitive Performance in Geriatric Patients—A Randomized Controlled Trial - Behrendt, Tom; Bielitzki, Robert; Behrens, Martin; Glazachev, Oleg S.; Schega, Lutz (Frontiers in Physiology, 2022)
Background: It was recently shown that intermittent hypoxic-hyperoxic exposure (IHHE) applied prior to a multimodal training program promoted additional improvements in cognitive and physical performance in geriatric patients compared to exercise only. However, there is a gap in the literature to which extent the addition of IHHE can enhance the effects of aerobic training. Therefore, the aim of this study was to investigate the efficacy of IHHE applied prior to aerobic cycling exercise on cognitive and physical performance in geriatric patients. Methods: In a randomized, two-arm, controlled, and single-blinded trial, 25 geriatric patients (77-94 years) were assigned to two groups: IHHE group (IG) and control group (CG). Both groups completed 6 weeks of aerobic training using a motorized cycle ergometer, 3 times a week for 20 min per day. The IG was additionally exposed to intermittent hypoxic and hyperoxic periods for 30 min prior to exercise. The CG followed the similar procedure breathing sham hypoxia. Within 1 week before and after the interventions, cognitive performance was assessed with the Dementia-Detection Test (DemTect) and the Clock-Drawing Test (CDT), while physical performance was measured using the Timed “Up and Go” Test (TUG) and the Short-Physical-Performance-Battery (SPPB). Results: No interaction effect was found with respect to the DemTect (p²=0.02). An interaction effect with medium effect size (p²=0.08) was found for CDT performance with a higher change over time for IG (d=0.53) compared to CG (d=0.06). The ANCOVA with baseline-adjustment indicated between-group differences with a large and medium effect size at post-test for the TUG (p²=0.29) and SPPB (p²=0.06) performance, respectively, in favour of the IG. Within-group post-hoc analysis showed that the TUG performance was worsened in the CG (d=0.65) and remained unchanged in the IG (d=0.19). Furthermore, SPPB performance was increased (d=0.58) in IG, but no relevant change over time was found for CG (d=0.00). Discussion: The current study suggests that an additional IHHE prior to aerobic cycling exercise seems to be more effective to increase global cognitive functions as well as physical performance and to preserve functional mobility in geriatric patients in comparison to aerobic exercise alone after a 6-week intervention period.